Función de las acuaporinas durante la CRIOPRESERVACIÓN en el semen del caballo, cerdo y toro (monografía) (2022)
The cryopreservation of semen has evolved to become a technique Widely used in domestic mammals. To further improve the efficiency of the cryopreservation of spermatozoa, it is necessary to understand the molecular mechanisms that underlie the properties that generate the sperm cryoinjuries (Funji & et al. 2018). In this context, the AQP are important water channel-forming proteins that are directly involved in osmolarity therefore their absence or inhibition may be an important determinant of sperm death during changes temperature abrupt. (C.H. Yeung, Callies, Tuttelmann, Kliesch, & Cooper, 2010). Therefore, the main function of aquaporins in the process will be addressed. of cryopreservation in the semen of the equine, bovine and porcine species.